THE DEMOCRATIZATION OF THE ORGANIZATIONAL REGISTRATION OF INDIGENOUS BELIEFS FOR FULFILLING THE RIGHT OF CITIZENS - Tuti Widyaningrum; Khalimi Khalimi (Jurnal Dinamika Hukum, 2021)
In a democratic state, each person should ideally be equal before the law and government. ver, in Indonesia, this was not fully obtained by, Indigenous Beliefs or known as  Penghayat Kepercayaan terhadap Tuhan YME. The most significant obstacle for Indigenous Beliefs is to obtain the rights of organizational registration. Even though there is a Decree of the Constitutional Court No. 97/PUU-XIV/2016 that has equalized the position of religion and belief, there is still discrimination against Indigenous Beliefs. When they want to access their rights of citizens, they always encountered the requirements of organizational registration. This research seeks to investigate how to democratize organizational registration of Indigenous Beliefs followers in order to be able to create the equality and justice. This research employed a normative juridical method with a legal history approach to observe the extent of the historical context of the formation of legislation on Indigenous Beliefs followers’ organization.Keywords: Democracy; Indigenous Beliefs; Organization